Development of a mobile application for locating fire hydrant - Yeo, Kenneth Yao Long (2015)
In fire-fighting situations, the fire and rescue specialists need to connect to a fire hydrant in the vicinity to obtain the water supply needed. It is important to locate a fire hydrant as soon as possible to quickly put out the fire. A mobile application is developed so that the specialist is able to tap on the technology of the mobile phone to search for hydrants within his area quickly to put out the fire before it gets too late. This project has been submitted to the Ministry of Home Affairs Security Awareness For Everyone (SAFE) Program. The result of the program is that NTU got a Gold award for this mobile application.